Efficacy and safety of olokizumab in patients with rheumatoid arthritis with an inadequate response to TNF inhibitor therapy: outcomes of a randomised Phase IIb study. Issue 9 (18th March 2014) - Genovese, Mark C; Fleischmann, Roy; Furst, Daniel; Janssen, Namieta; Carter, John; Dasgupta, Bhaskar; Bryson, Judy; Duncan, Benjamin; Zhu, Wei; Pitzalis, Costantino; Durez, Patrick; Kretsos, Kosmas
Abstract : Objectives: The aim of this 12-week Phase IIb study was to assess the efficacy and safety of olokizumab (OKZ), a humanised anti-IL6 monoclonal antibody, in patients with rheumatoid arthritis (RA) with moderate-to-severe disease activity who had previously failed tumour necrosis factor (TNF) inhibitor therapy. The dose-exposure-response relationship for OKZ was also investigated. Methods: Patients were randomised to one of nine treatment arms receiving placebo (PBO) or OKZ (60, 120 or 240 mg) every 4 weeks (Q4W) or every 2 weeks (Q2W), or 8 mg/kg tocilizumab (TCZ) Q4W. The primary endpoint was change from baseline in DAS28(C-reactive protein, CRP) at Week 12. Secondary efficacy endpoints were American College of Rheumatology 20 (ACR20), ACR50 and ACR70 response rates at Week 12. Exploratory analyses included comparisons of OKZ efficacy with TCZ. Results: Across 221 randomised patients, OKZ treatment produced significantly greater reductions in DAS28(CRP) from baseline levels at Week 12, compared to PBO (p<0.001), at all the OKZ doses tested (60 mg OKZ p=0.0001, 120 and 240 mg OKZ p<0.0001). Additionally, ACR20 and ACR50 responses were numerically higher for OKZ than PBO (ACR20: PBO=17.1–29.9%, OKZ=32.5–60.7%; ACR50: PBO=1.3–4.9%, OKZ=11.5–33.2%). OKZ treatment, at several doses, demonstrated similar efficacy to TCZ across multiple endpoints. Most adverse events were mild or moderate and comparable between OKZ and TCZ treatment groups. Pharmacokinetic/pharmacodynamic modelling demonstrated a shallow dose/exposure response relationship in terms of percentage of patients with DAS28(CRP) <2.6. Conclusions: OKZ produced significantly greater reductions in DAS28(CRP) from baseline at Week 12 compared with PBO. Reported AEs were consistent with the safety profile expected of this class of drug, with no new safety signals identified. Trial register number: NCT01242488.